Assessment of antimicrobial resistance, biofilm formation, and surface modification potential in hospital strains of Pseudomonas aeruginosa and Klebsiella pneumoniae - Lordelo, Roberta (2024)
The occurrence of healthcare-associated infections is a multifactorial phenomenon related to hospital space contamination by bacteria. The ESKAPE group, specifically Pseudomonas aeruginosa and Klebsiella pneumoniae, play a relevant role in the occurrence of these infections. Therefore, comprehensive research is needed to identify characteristics that justify the prevalence of these species in the healthcare environment. In this line, the study aimed to determine the antimicrobial resistance, biofilm formation, and the potential for polymer degradation in a collection of 33 P. aeruginosa strains and 2 K. pneumoniae strains sampled from various equipment and non-critical surfaces in a Portuguese hospital. Antimicrobial susceptibility tests revealed that none of the strains was categorized as multidrug-resistant (non-MDR). An assessment of their biofilm-forming capabilities indicated that 97 % of the strains exhibited biofilm-producing characteristics. Notably, within this group, the majority of P. aeruginosa and half of K. pneumoniae strains were classified as strong biofilm producers. Furthermore, the strains were evaluated for their potential to cause damage or change medical devices, namely infusion sets, nasal cannula, and urinary catheters. Three P. aeruginosa strains, two strong and one moderate biofilm producers, showed the highest ability to modify surfaces of the nasal cannula and infusion sets. Additionally, the Chi-square test revealed a statistically significant relationship between the presence of P. aeruginosa strains and the water accession spots. In conclusion, this work suggests that bacteria from this group hold a significant ability to grow in the healthcare environment through the degradation of non-critical materials. This suggests a potential concern for the persistence and proliferation of these organisms in hospital environments, emphasizing the importance of robust infection control measures to mitigate the risks associated with bacterial growth on such surfaces.